08.28 The prognostic value of iga autoantibodies (rheumatoid factor and acpa) for prediction of the therapeutic response to anti-tnf therapy in patients with rheumatoid arthritis. (1st March 2017) - Sieghart, Daniela; Studenic, Paul; Alasti, Farideh; Horn, Thomas; Haslacher, Helmut; Aletaha, Daniel; Smolen, Josef; Steiner, Günter
Abstract : Background and aim: Anti-citrullinated protein antibodies (ACPA) and rheumatoid factor (RF) are important diagnostic markers in rheumatoid arthritis (RA). These antibodies are predominantly of the IgM (RF) or IgG (ACPA) isotype while the diagnostic value of IgA antibodies appears to be limited. However, IgA autoantibodies might have some prognostic value. This study aimed to investigate the predictive value of RF and ACPA IgA antibodies regarding response to treatment in patients with RA. Methods: 255 patients who had undergone at least one treatment with TNF inhibitors were tested for the presence of IgA-RF and IgA-ACPA by EliA (Thermo Fisher Scientific). IgM-RF and IgG-ACPA were routinely measured by nephelometry and the anti-CCP assay, respectively. To define response to therapy SDAI50 and ACR20 responses were calculated. Results: Among the 255 patients 114 (44.7%) were found to be IgA-RF positive: 12 of them were negative for IgM-RF and 6 patients were double negative for IgM-RF and IgG-IgG. IgA-ACPA were detected in 79 (31%) patients and almost all of them had also IgG-ACPA. Together, 49% of the patients had at least one type of IgA antibody. In total, 59% of RA patients were positive for RF by nephelometry. Testing for IgA-RF did identify additional 5% of RF positive patients and might therefore have some added diagnostic value. Remarkably, the percentage of patients showing a SDAI50 response to anti-TNF treatment was significantly lower in patients positive for IgA-RF and/or IgA-ACPA (p<0.0001) compared to IgA-negative patients among whom 58% showed a SDAI50 response. Patients positive for IgA-ACPA but negative for IgA-RF had the lowest response rate with only one out of nine patients showing a response. Similar results were obtained when ACR20 was used as response criterium. In contrast, no difference between the groups was observed with respect to treatment with methotrexate and other synthetic drugs. Conclusion: IgA antibodies were found in approximately 50% of the tested patient collective and identified additional 5% of RF positive patients. IgA-RF and particularly IgA-ACPA appear to have predictive value regarding the therapeutic response to TNF inhibitory biological drugs and could help in further stratification of RA patients and therapeutic decision making.